Spatial Planning for Agricultural Development Based on Carrying Capacity of Ecosystem Services in The Melolo Transmigration Area, East Sumba - Afifatur Rojikhah; Amin Setyo Leksono; Arief Rachmansyah (Universitas Diponegoro, 2024)
Transmigration is one of the government programs that aim to create a new growth center by establishing an activity center through the development of basic business patterns. Development of the main business pattern is carried out through the management of land resources for agriculture. Improper management of land resources can lead to a decrease in environmental quality. Therefore, it is necessary to know the potential carrying capacity of ecosystem service to plan agricultural development. Parameters are used to analyze the carrying capacity of ecosystem services as provisioning based on environmental services for water and food provisioning. The environmental service assessment method for water and food provisioning is calculated using weighting and scoring. The total value of the carrying capacity of ecosystem services as provisioning is obtained from the calculation of the two parameters using the Simple Additive Weighting method. The results of the analysis show that the value of the carrying capacity of ecosystem service as provisioning is classified as very low. This indicates that the capability of the land for agricultural development is very low. Agricultural development requires conservation actions to increase the carrying capacity of ecosystem service. Recommendations for conservation actions are carried out through land use arrangements.